Influence of practice time on surfing injuries - Natacha Verônica Bazanella; José Guilherme Zanella D'Almeida Garrett; Anna Raquel Silveira Gomes; Luiz Fernando Novack; Raul Osiecki; Raciele Ivandra Guarda Korelo
Abstract Introduction: studying the influence of surfing on the prevalence of injuries may contribute to prevention. Objective: to analyze the influence of time practicing sports and the occurrence of previous surgery on the profile and prevalence of injuries caused by surfing. Methods: Sixty-six Brazilian surfers (26.16 ± 0.73 years old) participated in this study. Anthropometric data, physical activity level, surfing practice time and the prevalence of injuries (type of injury, anatomical region affected, and mechanism of injury) were evaluated. To assess which of the studied variables exerted significant influence on the mean number of injuries, a Poisson log-linear model was adjusted through R software (p < 0.05). Results: most surfers were classified as eutrophic (73%), very active (60.6%), had an average practice time of 10.1 ± 1 years, and were not members of a surfing federation (74%). It was also observed that 90.9% of participants reported injuries caused by surfing and 44.9% affected the lower limbs. The majority of these injuries affected the integumentary system (46.6%). The main mechanism of injury was impact with the board or seabed (40.4%). Furthermore, it was found that surfing federation members presented an average of 58.4% more injuries than non-members (p = 0.007). Surfers who had undergone previous surgeries showed an average number of injuries that was 56.9% higher than other surfers (p = 0.012). In addition, it was found that for each extra year of surfing, the average number of injuries increased by 2.5% (p = 0.0118). Conclusion: the average number of injuries increased with increment in time practicing the sport, previous surgery and membership in a surfing federation.